PENILAIAN KINERJA TRIPLE BOTTOM LINE PERUSAHAAN HIGH PROFILE DAN LOW PROFILE YANG LIST DI BEI - Sri Wahjuni Latifah (ITB AAS INDONESIA, 2019)
This research is conducted with the aim of analyzing the performance of companies in Indonesia if measured by Triple Bottom Line and testing whether companies with high environmental risk (high profile type) have different performance with companies with low environmental risk (low profile type). Triple Bottom Line performance is measured by the GRI-G4 Index. The data were obtained from companies listed on the Indonesia Stock Exchange in 2017 and the research sample was conducted with purposive technique and obtained 42 companies. Data is obtained by downloading Financial reports and CSR Report at www.idx.co.id. Data analysis was done by descriptive statistic and Independent Sample T Test. The results showed that performance based on Triple Bottom Line in Indonesia in 2017 was low (24%). Whereas, if observed on performance differences in companies with high profile type with low profile type, profit performance measured by economic aspects and the performance of planets measured by environmental aspects is unlikely. While the performance of people measured by social aspect shows difference between high profile company and low profile.